1991
DOI: 10.1103/revmodphys.63.239
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological theory of unconventional superconductivity

Abstract: This article is a review of recent developments in the phenomenological description of unconventional superconductivity.Starting with the BCS theory of superconductivity with anisotropic Cooper pairing, the authors explain the group-theoretical derivation of the generalized Ginzburg-Landau theory for unconventional superconductivity. This is used to classify the possible superconducting states in a system with given crystal symmetry, including strong-coupling effects and spin-orbit interaction. On the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
2,200
5
8

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 2,075 publications
(2,263 citation statements)
references
References 151 publications
(169 reference statements)
50
2,200
5
8
Order By: Relevance
“…For a superconducting transition at T c we need α, β 1 > 0. If further β 2 < 0 then a d x 2 −y 2 -or a d xy -wave state would arise, whereas for β 2 > 0 the complex combinations d x 2 −y 2 ± id xy is energetically favored [35]. For both graphene around the van Hove singularity [43] and for generic circular Fermi surfaces on the hexagonal lattice [86], it has been shown that β 2 > 0, and thus the chiral d x 2 −y 2 ± id xy -wave combination is the widely favored solution.…”
Section: Order Parameter Symmetriesmentioning
confidence: 99%
See 3 more Smart Citations
“…For a superconducting transition at T c we need α, β 1 > 0. If further β 2 < 0 then a d x 2 −y 2 -or a d xy -wave state would arise, whereas for β 2 > 0 the complex combinations d x 2 −y 2 ± id xy is energetically favored [35]. For both graphene around the van Hove singularity [43] and for generic circular Fermi surfaces on the hexagonal lattice [86], it has been shown that β 2 > 0, and thus the chiral d x 2 −y 2 ± id xy -wave combination is the widely favored solution.…”
Section: Order Parameter Symmetriesmentioning
confidence: 99%
“…It preserves full SU(2) spin-rotation symmetry, as long as the normal state is spindegenerate. However, it breaks time-reversal symmetry since the time-reversal operator K acts as K∆(k) = ∆ * (−k) on a spin-singlet order parameter [35]. It thus belongs to class C in the Altland-Zirnbauer classification of Bogoliubov-de Gennes systems [112,113].…”
Section: Non-trivial Topologymentioning
confidence: 99%
See 2 more Smart Citations
“…where Q( k) = 1/ √ 4| q|(| q| + q z ) and σ are the Pauli matrices [11]. In the particle-hole basis, the eigenstates ofˆ ( k) are…”
Section: Btk Theorymentioning
confidence: 99%